PENGARUH HARI LIBUR KEAGAMAAN TERHADAP RETURN SAHAM DAN TRADING VOLUME ACTIVITY (TVA) (Studi pada Saham yang terdaftar dalam kelompok Perusahaan LQ45) - Samhaji Samhaji; Mohammad Amin; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2018)
ABSTRACTThis research was conducted on the LQ45 group companies listed on theIndonesia Stock Exchange during 2015-2017 with the title "The Effect ofReligious Holidays on Stock Returns and Trading Volume Activity (TVA)".The purpose of this study is the first to find out the difference between theaverage abnormal return obtained by investors before and after the ReligiousHolidays on the IDX. Second is to find out the difference between the averagestock trading volume activity before and after the Religious Holidays on the IDX.The data analysis method used in this research is the t test (Paired Sample t-test).The results of data analysis and discussion of the results of research thathas been done, it can be concluded that there are no differences before and afterthe Religious Holidays on Abnormal Return and Trading Volume Activity (TVA).This shows that none of the stock trading days has a significant effect on LQ45company's stock returns during the period 2015 to 2017.Keywords: Religious Holidays, Stock Returns, Trading Volume Activity (TVA).